The Fragmentation of Aid - Mahn, Timo Casjen. author. aut Link
XXVI, 359 p. 10 illus., 2 illus. in color.
Keywords: This edited volume provides an assessment of an increasingly fragmented aid system. Development cooperation is fundamentally changing its character in the wake of global economic and political transformations and an ongoing debate about what constitutes, and how best to achieve, global development. This also has important implications for the setup of the aid architecture. The increasing number of donors and other actors as well as goals and instruments has created an environment that is increasingly difficult to manoeuvre. Critics describe today's aid architecture as 'fragmented': inefficient, overly complex and rigid in adapting to the dynamic landscape of international cooperation. By analysing the actions of donors and new development actors, this book gives important insights into how and why the aid architecture has moved in this direction. The contributors also discuss the associated costs, but also potential benefits of a diverse aid system, and provide some concrete options for the way forward.